2009
DOI: 10.1007/s12618-009-0008-1
|View full text |Cite
|
Sign up to set email alerts
|

ADHD and comorbid depression

Abstract: Attention-defi cit/hyperactivity disorder (ADHD) is prevalent, chronic, and often comorbid with other disorders. This article reviews the literature on ADHD and comorbid major depressive disorder from childhood through adolescence and adulthood. We also report fi ndings from a study we conducted that examined the prevalence of ADHD and comorbid major depression in adults. Diagnostic history data were analyzed in 524 adults (308 men; 216 women), 383 of whom had a diagnosis of ADHD. Adults with ADHD were more li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 56 publications
0
3
0
Order By: Relevance
“…The prevalence of any of the considered comorbid psychiatric disorders in adults with ADHD ( n =335) was reported to be significantly higher than in those without (49% vs 33%). This included a significantly higher prevalence of anxiety disorders (23%) and depressive illness (19%) [46]. A population‐based sample ( n =30,532) including people with ID (3.8%) found anxiety disorders (37.9%) to be the most prevalent co‐morbidity with ADHD [47].…”
Section: Co‐morbidities Associated With Epilepsy and Nddsmentioning
confidence: 99%
“…The prevalence of any of the considered comorbid psychiatric disorders in adults with ADHD ( n =335) was reported to be significantly higher than in those without (49% vs 33%). This included a significantly higher prevalence of anxiety disorders (23%) and depressive illness (19%) [46]. A population‐based sample ( n =30,532) including people with ID (3.8%) found anxiety disorders (37.9%) to be the most prevalent co‐morbidity with ADHD [47].…”
Section: Co‐morbidities Associated With Epilepsy and Nddsmentioning
confidence: 99%
“…On the other hand, boys with ADHD also took more responsibility than typically developing children for negative parent-child interactions. Previous research has shown that boys with ADHD are more likely to experience internalizing problems such as depressive or anxiety symptoms than typically developing control children (e.g., [48,49]) and perhaps related to these internalizing problems, children with ADHD assume greater personal responsibility for negative family events. As such, it is possible that different mechanisms underlie ADHD boys' higher ratings of child responsibility attributions for positive versus negative parenting behaviors (positive bias and depressive distortions).…”
Section: Differences Between Children With and Without Adhdmentioning
confidence: 99%
“…During the past couple of decades, many countries have witnessed females catch up with and even surpass males in many aspects of educational achievement including language (Cole, 1997;Gibb, Fergusson & Horwood, 2008;Peacock & Ho, 2003). Of particular note, individual differences in foreign language learning research has recognized gender-based differences in factors such as motivation (Dörnyei, 2003), learning strategies (Oxford, 1993;Oxford &Ehrman, 1995;Peacock & Ho, 2003) and foreign language classroom anxiety (Park & French, 2013).…”
Section: Introductionmentioning
confidence: 99%